(untitled) (Tzintzun. Revista de Estudios Históricos, 2016)
The author of this paper demonstrates the complex relations and interests that emerge from the strategies adopted by the agrarian and industrial elite, the middle level agrarian bourgeoisie and colonists that worked to bring about the scientific development of the sugar industry in Cuba in the second half of the 19th century. She also emphasizes the repercussions of such ideas on the discourse generated by reform-minded intellectuals and agricultura! engineers of the time. It should be said that sorne of the latter participated in the changes that affected the industry. As a result, their agrarian proposals carne to reflect very clearly the national reality of the insular economy of the period; to the point that sorne students of the evolution of doctrines in Cuba classify such individuals as the true economic thinkers of that era.